Vaccination herd effect experience in Latin America: a systematic literature review - Rodrigo DeAntonio; Sylvia Amador; Eveline M. Bunge; Jennifer Eeuwijk; David Prado-Cohrs; Javier Nieto Guevara; Maria del Pilar Rubio; Eduardo Ortega-Barria (Taylor & Francis Group, 2019)
Background: National pediatric vaccination programs have been introduced in Latin America (LatAm) to reduce the burden of diseases due to pathogens such as rotavirus, Haemophilus influenzae type b (Hib) and pneumococcus. Vaccination health benefits may extend to unvaccinated populations by reducing pathogen transmission. Understanding herd effect is important for implementation and assessment of vaccination programs. The objective was to conduct a systematic review of published epidemiological evidence of herd effect with Hib, rotavirus and pneumococcal conjugate vaccines (PCV) in LatAm. Methods: Searches were conducted in PubMed, Virtual Health Library (VHL), SciELO and SCOPUS databases, for studies reporting data on herd effect from Hib, rotavirus and PCV vaccination in LatAm, without age restriction. Searches were limited to articles published in English, Spanish or Portuguese (1990-2016). After screening and full-text review, articles meeting the selection criteria were included to be critically appraised following criteria for observational and interventional studies. The presence of a herd effect was defined as a significant decrease in incidence of disease, hospitalization, or mortality. Results: 3,465 unique articles were identified, and 23 were included (Hib vaccine n = 5, PCV n = 8, rotavirus vaccine n = 10). Most studies included children and/or adolescents (age range varied between studies). Studies in adults, including older adults (aged > 65 years), were limited. Few studies reported statistically significant reductions in disease incidence in age groups not targeted for vaccination. Hib-confirmed meningitis hospitalization decreased in children but herd effect could not be quantified. Some evidence of herd effect was identified for PCV and rotavirus vaccine in unvaccinated children. Evidence for herd effects due to PCV in adults was limited. Conclusion: After introduction of Hib, PCV and rotavirus vaccination in LatAm, reductions in morbidity/mortality have been reported in children not targeted for vaccination. However, due to methodological limitations (e.g. short post-vaccination periods and age range studied), there is currently insufficient evidence to quantify the herd effect in adult populations. More research and higher quality surveillance is needed to characterize herd effect of these vaccines in LatAm.